P53 deficiency potentiates LPS-Induced acute lung injury in vivo - Uddin, Mohammad A. (Curr Res Physiol, 2020)
Acute Lung Injury (ALI) and Acute Respiratory Distress Syndrome (ARDS) represent a significant cause of morbidity and mortality in critically ill hospitalized patients. Emerging evidence suggest that the expression levels of P53 in the lungs are associated with the supportive effects of heat shock protein 90 inhibitors and growth hormone releasing hormone antagonists in the endothelium. In the current study, we employed an in vivo model of intratracheal administration of lipopolysaccharides (LPS)-induced ALI to investigate the role of P53 in counteracting LPS-induced lung inflammatory responses. In wild type mice, LPS induced the expression of IL-1α, IL-1β, and TNFα in the lungs, increased bronchoalveolar lavage fluid protein concentration, and activated cofilin. Remarkably; those responses were more potent in P53 knockout mice, suggesting the crucial role of P53 in orchestrating rigorous endothelial defenses against inflammatory stimuli. The present study supports previous endeavors on the protective role of P53 against lung inflammatory disease, and enrich our knowledge on the development of medical countermeasures against ARDS.